2000
DOI: 10.7326/0003-4819-132-6-200003210-00003
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Iloprost To Treat Severe Pulmonary Hypertension: An Uncontrolled Trial

Abstract: Inhaled iloprost may offer a new therapeutic option for improvement of hemodynamics and physical function in patients with life-threatening pulmonary hypertension and progressive right-heart failure that is refractory to conventional therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0
19

Year Published

2002
2002
2005
2005

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 247 publications
(131 citation statements)
references
References 28 publications
3
109
0
19
Order By: Relevance
“…4,11,[13][14][15] Several open-label, uncontrolled studies of patients with severe pulmonary hypertension suggested that longterm use of aerosolized iloprost results in substantial clinical improvement. 11,13,[16][17][18][19][20] Our objective in this trial was to evaluate the effects of inhaled iloprost using a rigorous end point of clinical efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…4,11,[13][14][15] Several open-label, uncontrolled studies of patients with severe pulmonary hypertension suggested that longterm use of aerosolized iloprost results in substantial clinical improvement. 11,13,[16][17][18][19][20] Our objective in this trial was to evaluate the effects of inhaled iloprost using a rigorous end point of clinical efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment with prostanoids has been shown to improve prognosis, exercise capacity, and hemodynamic variables. 2,3 The mechanisms of action, however, are not fully understood so far, in addition to vasodilatation antiproliferative effects have been hypothesized. 2 Endothelin-1 (ET-1) is a potent endogenous vasoconstrictor and smooth-muscle mitogen 4 that is overexpressed in the plasma and lung tissue of patients with PAH.…”
mentioning
confidence: 99%
“…In idiopathic PAH, short-term inhalation of iloprost resulted in greater pulmonary vasodilatation than did nitric oxide (65). For long-term use, the relatively short duration of action of inhaled iloprost necessitates 6 to 9 inhalations per day (66,67). In a 3-month multicenter trial, iloprost administered in a dosage of 2.5 or 5 g 6 or 9 times daily improved the 6-min walking distance and NYHA functional class (68).…”
Section: Prostanoidsmentioning
confidence: 99%